2017
DOI: 10.5114/aoms.2017.68972
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailable testosterone is independently associated with Fatty Liver Index in postmenopausal women

Abstract: IntroductionPrevious studies have examined the correlation between hyperandrogenemia and non-alcoholic fatty liver disease (NAFLD) in women and showed contradictory results. Therefore, we aimed to evaluate the relationship between testosterone level and Fatty Liver Index (FLI), as a surrogate marker for NAFLD, in a cohort of postmenopausal women.Material and methodsA total of 150 postmenopausal women were included in this cross-sectional study. Anthropometric and biochemical parameters, as well as blood pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
60
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(69 citation statements)
references
References 39 publications
(45 reference statements)
4
60
0
2
Order By: Relevance
“…Increased visceral fat mass is a source of proinflammatory adipocytokines [5][6][7][8], exerting a low-grade inflammation environment which could predispose to the future hypertension occurrence [9]. In addition, increased abdominal fat mass is accompanied with increased insulin resistance [4,8]. However, even though previous studies confirmed the association between obesity and hypertension, the underlying pathophysiological mechanism is not well elucidated [10,11].…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…Increased visceral fat mass is a source of proinflammatory adipocytokines [5][6][7][8], exerting a low-grade inflammation environment which could predispose to the future hypertension occurrence [9]. In addition, increased abdominal fat mass is accompanied with increased insulin resistance [4,8]. However, even though previous studies confirmed the association between obesity and hypertension, the underlying pathophysiological mechanism is not well elucidated [10,11].…”
Section: Introductionmentioning
confidence: 88%
“…The current cross-sectional study derived from our previous works investigating the utility of examining cardiometabolic markers in postmenopausal women [1][2][3][4][5][6][7]. A total of 150 postmenopausal women nontreated with medications (among them 44.7% hypertensive) were included in cross-sectional study.…”
Section: Study Populationmentioning
confidence: 99%
See 3 more Smart Citations